Competition Law Objectives in Kazakhstan - Lombardi, Claudio (Право и государство, 2020)
This article analyses the current competition law objectives of Kazakhstan and compares them to those of other jurisdictions, including the EU and the EAEU. The discourse around the competition law objectives in Europe and in the US has been ongoing for a long time. From a normative perspective the EU Treaties do not confine competition law to the pursuit of a specific aim, neither they explicitly define its object. Hence, scholars, public officials, and practitioners have long grappled with this interpretative conundrum. Since its inception, the main goal of EU competition law was the integration of the internal market. Moreover, according to the CJEU's case law and the Treaties, competition law has a number of other objectives, including economic freedom, economic efficiency, justice and fairness. However, the broad spectrum of the different issues that may be categorised as been part of these objectives led to the formulation of narrower theories. In particular, one prevailed over the others, in the last decade, which comes under the name of consumer welfare theory. In a 2010 speech, after being nominated commissioner in charge of competition policy, Vice-President Almunia said that competition policy is a tool at the service of consumers and that consumer welfare is at the heart this policy and its achievement drives the Commission's priorities and guides their decisions. Moreover, in its «General Guidelines » (a non-binding guidance paper), the Commission stated that the objective of Article 101 TFEU is to protect competition on the market as a means of enhancing consumer welfare and of ensuring an efficient allocation of resources. By contrast, in Kazakhstan the competition policy objectives have not received similar attention and have been rarely discussed by scholars and judges alike. This article explains the importance of setting clear goals for competition law enforcement and policy. Finally, it argues that the antitrust law objectives of Kazakhstan should differ from those established in the EU and the US, in particular aiming at sustainable development, growth, innovation, and redistribution.
Keywords: competition law; antitrust; antimonopoly law; objectives; public interest; economic objectives; competition enforcement; development; growth; innovation; distribution